Understanding international exit from a non-economic and emotional perspective: the case of Taiwanese entrepreneurs exit China - Lin, Yangpei (The University of Edinburgh, 2015)
I investigate why Taiwanese entrepreneurs who have invested in China exit. Viewed from the non-economic perspective, there are three main themes in this thesis. Theme A focuses on the non-economic variables in international exit. Theme B examines how incident-generated emotions shape entrepreneur’s actions in internationalization. Theme C presents an overview of the decision-making of international exit, summarizing the finding in Theme A and Theme B and revisiting the theoretical framework developed in literature chapter. Driven by the nature of the research questions, a multiple-case study methodology was adopted for the purpose of theory building. I employ the method of critical incident technique to explore firm’s critical events in internationalization and how entrepreneurs feel and respond to. In total, I identify five exit cases and two stay cases. 34 semi-structured in-depth interviews were conducted with entrepreneurs and their stakeholders. Data was coded in an interactive manner, working back and forth between theory, emerging patterns and data. Other sources including annual reports, press release, webpage, meeting minutes and archives are used for data triangulation. Being positioned at the intersection of entrepreneurship and international business research paths, this research firstly examines international business literature and use theories in entrepreneurship field to explain my data. Following Gimeno et al.’s (1997) threshold of performance theory, entrepreneurs can terminate an economically profitable business since it no longer meets entrepreneur’s expectation. My finding shows in addition to organizational performance, entrepreneur’s personal goal, predisposition of China and family socio-emotional wealth can influence the international exit decision by changing entrepreneur’s threshold of performance and the non-economic value of the firm. This explains why some entrepreneurs shut down a profitable firm. Following entrepreneurial emotions literature (e.g. Baron, 2008; Foo et al., 2009), I examine how entrepreneur’s incident-generated emotions shape their behaviour in internationalization. Passion and confidence are positive for organizational growth while fear and disgust are negative for entrepreneur’s efforts in internationalization. Empathy is positive for learning and adaption and anger encourages risky actions with optimistic prediction. This section provides empirical evidence to entrepreneurial emotion studies and connects empathy with entrepreneur’s learning and development of institution-specific capability. Finally, I revisit the international exit decision-making framework and redefine international exit. My finding shows entrepreneurs who have positive emotional memory and predisposition of China are easier to recover and learn from their international exit experience and use it to renter into China in the future. Taken together, this thesis provides fresh insights into an emerging debate relating to international exit, particularly on emerging market studies. It contributes to the international business literature by viewing from non-economic perspective, indicating why some entrepreneurs persist in a failing venture while others shut down a profitable venture. This research also adds to entrepreneurial emotion literature by providing an insight to positive and negative emotions and focusing on specific emotions rather than a broad category, describing six emotions and their effects on entrepreneur’s decision in internationalization. Implications for practitioners and policy makers are also discussed.
Keywords: decision-making; emotions; international exit